EFEKTIVITAS PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA PADA MASA PANDEMI COVID 19 DI DESA KRUCIL KABUPATEN PROBOLINGGO - Nurhafiva Nurhafiva; Sri Juni Woro Astuti; Mohammad Natsir (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The purpose of this study was to determine the inhibiting and supporting factors for the Village Fund Direct Cash Assistance program for the poor affected by Covid 19 in Krucil Village, Krucil District, Probolinggo Regency. In addition to knowing the effectiveness of the Village Fund Direct Cash Assistance program for the poor affected by Covid 19 in Krucil Village, Krucil District, Probolinggo Regency. The type of research used is a type of qualitative research. The research approach used in this research is descriptive qualitative. The government has designed various new policies in order to suppress the spread and deal with this virus. Among them is Law Number 2 of 2020 concerning the Stipulation of Government Regulations in Lieu of Law Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid 19) Pandemic. In addition, in order to protect the poor, the government is expanding the Social Safety Net (JPS) including what is stated in the Regulation of the Minister of Village of PDTT Number 6 of 2020 concerning Amendments to the Regulation of the Minister of Village of PDTT Number 11 of 2019 concerning Priority for the Use of Village Funds which among other things relates to the provision of Direct Cash Assistance sourced from the Village Fund (BLT-Village Fund).